Clarifying the Concept of Well-Being: Psychological Need Satisfaction as the Common Core Connecting Eudaimonic and Subjective Well-Being. Issue 4 (December 2019) - Martela, Frank; Sheldon, Kennon M.
Interest in the experience of well-being, as both a research topic and as a policy goal, has significantly increased in recent decades. Although subjective well-being (SWB)—composed of positive affect, low negative affect, and life satisfaction—is the most commonly used measure of well-being, many experts have argued that another important dimension of well-being, often referred to as eudaimonic well-being (EWB), should be measured alongside SWB. EWB, however, has been operationalized in at least 45 different ways, using measures of at least 63 different constructs. These diverse measurement strategies often have little overlap, leading to discrepant results and making the findings of different studies difficult to compare. Building on the Eudaimonic Activity Model, we propose a tripartite conception of well-being, distinguishing between eudaimonic motives/activities, psychological need satisfaction, and SWB, arguing that the needs category provides a parsimonious set of elements at the core of the well-being construct. Based on the self-determination theory claim that all human beings share evolved psychological needs for autonomy, competence, and relatedness, we show that satisfaction of all three needs directly affect SWB and other health and wellness outcomes, can efficiently explain the effects of various behaviors and conditions upon well-being outcomes, and are universally impactful across cultures. We conclude that routinely measuring psychological needs alongside SWB within national and international surveys would give policymakers a parsimonious way to assess eudaimonic dimensions of wellness and provide powerful mediator variables for explaining how various cultural, economic, and social factors concretely affect citizens' well-being and health.